Potential of Nonthermal Atmospheric-Pressure Dielectric Barrier Discharge Plasma for Inhibition of Athelia rolfsii Causing Southern Blight Disease in Lettuce - Salit Supakitthanakorn; On-Uma Ruangwong; Choncharoen Sawangrat; Wimada Srisuwan; Dheerawan Boonyawan (Agriculture, 2023)
Athelia rolfsii is one of the most destructive and aggressive fungal pathogens worldwide and causes southern blight disease of lettuce. A nonthermal atmospheric-pressure dielectric barrier discharge (DBD) plasma has attracted interest as an alternative control method to chemical usage because of its antimicrobial activity. Exposure of A. rolfsii to DBD plasma for 5, 10, 15, and 20 min resulted in in vitro fungal inhibition of mycelial discs and sclerotia. The results showed that DBD plasma exposure for 10 min completely inhibited fungal growth of mycelial discs, whereas exposure for over 20 min was required to inhibit the hyphal growth of sclerotia. Scanning electron microscopy (SEM) observations of mycelia and sclerotia abnormalities revealed laceration and damage of both mycelia and sclerotia. In addition, disease incidence and severity were reduced in mycelial and sclerotia inoculation following DBD plasma exposure for 15 and 20 min, respectively, compared with the positive control. In conclusion, the DBD plasma demonstrates antifungal activity against A. rolfsii via inhibition of fungal growth and reduction in disease incidence and severity. Therefore, DBD plasma has the potential to be applied in controlling southern blight disease of lettuce.